Evaluation of Ultrasonic Velocity Theories on Binary Liquid Mixtures of Propiophenone with Isomeric Xylenes at Temperatures (T = 303.15 to 318.15 K) - Gayatri Devi, Nanduri; Srinivasa Rao, N.V.N.B.; Ramachandran, D. (Asian Journal of Chemistry, 2020)
Densities (ρ), ultrasonic speeds of sound (u) of binary mixtures containing propiophenone with o-xylene, m-xylene and p-xylene were measured over the entire composition range at temperatures from 303.15-318.15 K and at atmospheric pressure 0.1 MPa. Experimental data of ultrasonic velocity was used to compute the theoretical velocities by using the various theories like Nomoto’s relation (UNOM), impedance relation (UIMP), Van Dael and Vangeel’s relation (UVDV), Rao’s specific velocity relation (URAO), Jouyban-Acree’s (UJOE) and Junjie’s theory (UJUN). The results are in good agreement with the experimental data. The relative percentage error, chi square test for goodness of fit and the molecular interaction parameter (α) values for non-ideality in the binary mixtures were computed and analyzed in terms of intermolecular interactions between the molecules of the binary mixtures.